Analisis Pengaruh Pengalaman Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai dengan Semangat Kerja Sebagai Variabel Moderasi (Studi Pada Puskesmas Margorejo Metro Selatan) - Yuli Indah Saputri; Dharmawan; Fitriani (Jurnal Manajemen DIVERSIFIKASI, 2026)
The purpose of this study was to determine whether there was an influence of work experience and work discipline on employee performance, with work spirit as a moderating variable at Margorejo Metro Selatan Health Center. This study used quantitative research, and the number of samples used was 40 respondents. The data collection technique used a questionnaire, with data analysis using Validity Test, Reliability Test, Normality Test, Linearity Test, Homogeneity Test, MRA Interaction Test, R Determination Test, and Statistical Hypothesis Test. The results of this study indicate that (1) work experience has an influence and is significant on employee performance. (2) Work discipline has an influence and is significant on employee performance. (3) Work spirit, as a moderation variable, is able to moderate or strengthen work experience and employee performance. (4) Work spirit as a moderation variable is able to moderate or strengthen work discipline and employee performance.